Electron paramagnetic resonance of some ABX3 compounds - Köksal, F; Bahadir, S; Karabulut, B; Basaran, E; Yerli, Y (Elsevier Sci Ltd, 1999)
Electron paramagnetic resonance studies of NaMnCl3, KMnCl3, KCuCl3, NH4CuCl3 were made between 400 and 5 K. The peak-to-peak derivative linewidths of these substances were found to be 14, 70, 10 and 5 mT, respectively. The line splitting below 15 K in NaMnCl3 was attributed to hyperfine interaction with the Mn2+ nucleus. The g values and the peak-to-peak derivative linewidths of KMnCl3, KCuCl3 and NH4CuCl3 were found to be temperature independent within the limits of experimental errors. The g values of NaMnCl3 and KMnCl3 are isotropic, however, of KCuCl3 and NH4CuCl3 are slightly anisotropic at room temperature and their principal values were determined. Hyperfineless structure of the spectra and the broad linewidths seem to be mainly due to exchange interactions of Mn2+ and Cu2+ ions among themselves in the respective compounds. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: inorganic compounds; magnetic materials; electronic paramagnetic resonance (EPR); magnetic properties